2019
DOI: 10.1088/1742-6596/1213/5/052042
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study of high/low temperature effects on the dynamic performance of rubber spring for railway vehicles

Abstract: For the layer rubber spring of a high-speed bogie, lab tests were conducted to obtain the dynamic parameters under extremely high and low temperatures (-60°C∼60°C) to obtain the nonlinear stiffness and damping parameters relevant to the frequency, amplitude and temperature changes. It starts from introducing the rubber element dynamic parameter test equipment, test plan and test methods. The applied loads and the temperatures are discussed. Then both the static and dynamic tests were performed for the layer sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 2 publications
0
7
0
Order By: Relevance
“…e authors of [16][17][18] analyzed and studied the performance of rubber springs at low temperature; the results showed that low temperature has a significant effect on the properties of rubber. Österlöf et al [19][20][21] studied the relationship between the rubber model and temperature. Ding et al [22] modified the low-temperature modulus of rubber and proposed a method for predicting low-temperature stiffness.…”
Section: Introductionmentioning
confidence: 99%
“…e authors of [16][17][18] analyzed and studied the performance of rubber springs at low temperature; the results showed that low temperature has a significant effect on the properties of rubber. Österlöf et al [19][20][21] studied the relationship between the rubber model and temperature. Ding et al [22] modified the low-temperature modulus of rubber and proposed a method for predicting low-temperature stiffness.…”
Section: Introductionmentioning
confidence: 99%
“…Select 45 kN as the conversion standard, and calculate λ N•45 when the prepressure is 57 kN, 65 kN, 75 kN, and 85 kN according to the theoretical formula (18); use formula (19) to calculate the dynamic parameters and compare with the test value, as shown in Figure 12. is method is named the theoretical DFCC prediction method (Method 1).…”
Section: Error Analysis Of the Dfcc Methodmentioning
confidence: 99%
“…Select 45 kN as the conversion standard; according to the test data and formula (1), the static stiffness k st under different prepressures is calculated, and the ratio of test stiffness is further calculated to obtain λ N•45 ; refer to Table 2; use formula (19) to calculate the dynamic parameters and compare with the test value, as shown in Figure 13. is method is named the test DFCC prediction method (Method 2).…”
Section: Error Analysis Of the Dfcc Methodmentioning
confidence: 99%
See 2 more Smart Citations